Fiscal policy rules in a stock-flow consistent model - Kappes, Sylvio Antonio; Milan, Marcelo (Brazilian Keynesian Review, 2018)
The present paper analyzes four fiscal policy rules in a Stock-Flow Consistent model. The rules are: (i) government expenditures as a fixed proportion of GDP; (ii) government deficit as a fixed proportion of GDP; (iii) government debt as a fixed proportion of GDP; and (iv) a balanced budget. Then the economic trends implied by each rule are analyzed, and they are all compared. Some of the main findings can be summarized as follows: the more expansionist (or less contractionist) rules present higher growth rates, as expected; there is an inverse relationship between government debt and private debt, with the former being higher under the first rule, and lower in the balanced budget rule, the opposite happening in the case of private debt. Finally, considering enterprises’ profitability, we conclude that the best fiscal rule for firms is the first one, and, for the banking sector, also not surprisingly, it is the balanced budget rule.